1997
DOI: 10.1590/s0004-282x1997000500004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and quantitative analysis of the neurons of the myenteric plexus of the cecum of streptozotocin-induced diabetic rats

Abstract: The purpose of this work was to study the neurons of the myenteric plexus of the cecum of rats with chronic streptozotocin-induced diabetes. We used four experimental groups of animals. In groups D2 and D8 animals were killed two and eight months, respectively, after diabetes induction and groups C2 and C8 were used as controls. We carried out whole-mount preparations stained with Giemsa and NADH-diaphorase. We verified that the diabetes did not alter the shape and disposition of the myenteric ganglia; it prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
1
14

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 15 publications
7
46
1
14
Order By: Relevance
“…the absence of a significant difference in mean neuronal number for the large gastric curvature is related to the smaller density of neurons and the larger heterogeneity of their distribution when compared with the small gastric curvature; nevertheless, there was an undeniable neuronal decrease in the corpus of the stomach of diabetic rats. Some authors 11,12 observed a neuronal decrease in the cecum and duodenum, respectively, of rats with streptozotocininduced diabetes. Conversely, other authors 9 did not find a reduction in neuron number in the proximal colon of rats under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…the absence of a significant difference in mean neuronal number for the large gastric curvature is related to the smaller density of neurons and the larger heterogeneity of their distribution when compared with the small gastric curvature; nevertheless, there was an undeniable neuronal decrease in the corpus of the stomach of diabetic rats. Some authors 11,12 observed a neuronal decrease in the cecum and duodenum, respectively, of rats with streptozotocininduced diabetes. Conversely, other authors 9 did not find a reduction in neuron number in the proximal colon of rats under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin deficiency is also an explanation for the reduced dimensions observed here, once insulin is an anabolic hormone and, as such, a promoter of cellular development. On the other hand, there are reports that rats subjected to experimental diabetes have dimensional and weight increases of the small and large intestines 2,4,6,7,12 . The absence of hypertrophy of the proximal colon in this study could be related to factors such as the duration of the experimental period, the age of the animals and the moderate diabetic state.…”
Section: Discussionmentioning
confidence: 99%
“…Among those systems under investigation are the gastrointestinal tract and its intrinsic enteric nervous system, the neuronal network responsible for the control of the activities of the bowel. It is reported, for instance, that the myenteric neurons of the stomach, duodenum and cecum are numerically reduced in diabetes [1][2][3] , and that specific neurochemical groups show response patterns to diabetes which depend on the intestinal segment and the duration of the diabetic state [4][5][6][7] . These neuronal changes, as well as those associated to the autonomic innervation of the gut [8][9][10] , stand among the responsible by the clinical gastrointestinal symptoms of diabetes [11][12][13] .…”
mentioning
confidence: 99%
“…E-mail:jnzanoni@uem.br with induced colitis. Buttow et al (8) and Zanoni et al (38) found, respectively, a reduction in density of myenteric neurons in the duodenum and in the cecum of diabetic rats.…”
Section: Introductionmentioning
confidence: 97%